Build a friendship - Chapman, Sital Gorasia (Chapman, Sital Gorasia. Math adventurers., 2023)
"Beep the robot would love nothing more than to have her own pet, like her friends do. One morning she gets a surprise delivery--a parcel containing circles, squares, triangles, and pentagons for her to make her own robot cat! Beep realizes that she can't make a pet pal from flat, two-dimensional shapes so, with a flash of magic, the shapes become three-dimensional spheres, cubes, and pyramids. Join Beep as she tries different ways of putting shapes together to build her robot cat and make a best friend forever"--